Instructional technology: issues and challenges - Madarsha, Kamal Basha (Institut Terjemahan & Buku Malaysia Berhad, 2016)
This book is a compilation of materials on Instructional Technology (IT)contributed by authors who are considered as experts in this area. Hence, the title Instructional Technology: Issues and Challenges is apt and speaks volume, which you, the reader will find the reason why the author chose the title as you read through each and every chapter. In this book, each contributor examines different aspects of IT vis-a-vis the integral foundation which is Technology Assisted Teaching and Learning. These include sections related to social network such as Facebook, e-learning via smartphones and the like.